Influence of soluble or matrix‐bound isoforms of vascular endothelial growth factor‐A on tumor response to vascular‐targeted strategies. Issue 11 (10th July 2013) - Akerman, Simon; Fisher, Matthew; Daniel, Rachel A.; Lefley, Diane; Reyes‐Aldasoro, Constantino C.; Lunt, Sarah Jane; Harris, Sheila; Bjorndahl, Meit; Williams, Leigh J.; Evans, Helen; Barber, Paul R.; Prise, Vivien E.; et al.
Abstract : Antiangiogenic therapy based on blocking the actions of vascular endothelial growth factor‐A (VEGF) can lead to "normalization" of blood vessels in both animal and human tumors. Differential expression of VEGF isoforms affects tumor vascular maturity, which could influence the normalization process and response to subsequent treatment. Fibrosarcoma cells expressing only VEGF120 or VEGF188 isoforms were implanted either subcutaneously (s.c.) or in dorsal skin‐fold "window" chambers in SCID mice. VEGF120 was associated with vascular fragility and hemorrhage. Tumor‐bearing mice were treated with repeat doses of SU5416, an indolinone receptor tyrosine kinase inhibitor with activity against VEGFR‐2 and proven preclinical ability to induce tumor vascular normalization. SU5416 reduced vascularization in s.c. implants of both VEGF120 and VEGF188 tumors. However, in the window chamber, SU5416 treatment increased red cell velocity in VEGF120 (representing vascular normalization) but not VEGF188 tumors. SU5416 treatment had no effect on growth or necrosis levels in either tumor type but tended to counteract the increase in interstitial fluid pressure seen with growth of VEGF120 tumors. SU5416 pretreatment resulted in the normally fragile blood vessels in VEGF120‐expressing tumors becoming resistant to the vascular damaging effects of the tubulin‐binding vascular disrupting agent (VDA), combretastatin A4 3‐ O ‐phosphate (CA4P). Thus, vascular normalization induced by antiangiogenic treatment can reduce the efficacy of subsequent VDA treatment. Expression of VEGF120 made tumors particularly susceptible to vascular normalization by SU5416, which in turn made them resistant to CA4P. Therefore, VEGF isoform expression may be useful for predicting response to both antiangiogenic and vascular‐disrupting therapy. Abstract : What's new? Targeting the blood supply of tumors remains an important therapeutic strategy in the fight against cancer. Strategic approaches are aimed at vascular "normalization" primarily using compounds that interfere with the vascular endothelial growth factor (VEGF) pathway or vascular "disruption" using so‐called vascular disrupting agents (VDAs) agents. Using mice carrying tumors expressing specific isoforms of VEGF the authors show that the soluble 120 amino acids VEGF isoform is associated with susceptibility to vascular normalization induced by VEGFR‐2‐targeting treatment. Furthermore, normalization rendered tumor blood vessels resistant to subsequent treatment with an archetypal vascular disrupting agent, CA4P. These results suggest typing VEGF isoform expression in tumors may be useful to predict the response to vascular‐targeted therapy in patients.